Marshallese Beliefs, Perceptions, and Practices Related to Child Feeding Among Marshallese in the United States: Implications for Childhood Obesity. (February 2019) - Johnson, Kelly Vowell; Scott, Allison L; Shreve, Marilou; Ayers, Britni L; Seaton, Victoria S; McElfish, Pearl A
Introduction: Obesity affects more than 40 million children globally. Efforts to promote proper nutrition in an attempt to reduce childhood obesity should consider maternal beliefs and cultural customs around food. Little is known regarding child feeding, including weaning practices and foods consumed in the first years of life among Marshallese children, a sub-group of Pacific Islanders, residing in the United States. Methods: This study aims to explore the influences on introduction of complementary foods among Marshallese mothers and caregivers residing in the United States, to serve as the basis for promotion of improved nutrition. Focus groups and demographic surveys were conducted with Marshallese mothers and caregivers (N = 27) to explore child-feeding beliefs, perceptions, and practices. Results: All mothers reported breastfeeding their infants, and 80% reported using some type of milk supplementation. There was a difference in mother and caregiver responses regarding which first foods to introduce and average age of introduction. Discussion: Analysis revealed three themes identified as being influential for child-feeding practices: Marshallese breastfeeding customs, introduction of solid foods, and Marshallese family feeding customs.